PERANAN MANAJEMEN DALAM MEMAKMURKAN MASJID - Budi Firmansyah (Al Aqidah (Jurnal Studi Islam), 2019)
Management is needed in terms of achieving a goal, management can provide a very significant function in the prosperity of the mosque as well as the implementation of management in general, well-applied management will certainly have a positive impact but if management does not match its application it will lead to the failure of an objective. This study aims to determine the extent of the function of Management in the prosperity of the Mosque, the method in this study is descriptive qualitative, namely by direct observation at the research site and library research related to Management in the Prosperity of the Mosque.